Initial Stage Mentoring of Multi-Party Cooperative Pioneering for Women and MSMEs in Bantengputih Village, Karanggeneng District, Lamongan Regency - sumantri, bambang agus; Kiswardani, Wahyu Eka; Putri, Sekar Widyasari (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The target of this community service is women's groups and MSMEs in the Bantengputih Village area, Karanggeneng District, Lamongan Regency. The methods and stages of community service are focused on the formation and empowerment of groups for pioneering multi-party cooperatives. The community service stage is the preliminary stage. The results of the preliminary stage of this service related to the potential for empowering the target community are two, namely: the first potential, women's groups, the state of the workforce in 2024 in Bantengputih Village, women are 839 people. The second potential, MSMEs: based on data from the